Novel Three‐dimensional Sensor for Rapid Detection of Pb(II) and Cd(II) in Edible Mushrooms. Issue 5 (16th February 2021) - Yin, Jiaqi; Chu, Guanglei; Wang, Yue; Zhai, Hongguo; Wang, Bao; Sun, Xia; Guo, Yemin; Zhang, Yanyan
Abstract: A sensing platform was developed based on the molybdenum disulfide‐reduced graphene oxide (MoS2 ‐RGO). The flower‐like MoS2 ‐RGO nanocomposite had a large number of active sites such as oxygen‐containing groups and highly reactive sulfur that contributed to the adsorption and preconcentration of heavy metal ions (HMIs). MoS2 ‐RGO was synthesized by one‐step reduction method. Under optimized conditions, the limits of detection (LODs) for Pb(II) and Cd(II) was 0.13 μg/L and 0.59 μg/L with a linear range of 4.1–207.2 μg/L and 2.2–112.4 μg/L, respectively. The modified sensors had been successfully applied to detect Pb(II) and Cd(II) in three kinds of edible mushrooms. Abstract :